An assessment of livestock production sustainability in the Maghreb irrigated schemes - Sraïri M.T. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
In the Maghreb countries, because of structural drought, recent livestock production policies have relied heavily on irrigation. This aimed to secure animal protein supply by using water to grow fodder. Such choices have led many smallholder farms to rear cattle in typical dual purpose (both milk and meat) systems. In such a situation of fragmented supply, the usual tools available in developed countries to assess livestock production sustainability may not be adapted therefore, innovative methods have to be implemented. For that purpose, an array of indicators might be used, including economic profitability and water productivity through cattle and milk quality. All together, these parameters can be used to analyse beef supply chains in an eventful context.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)